Characterization of molecular biomarkers of mercury exposure to muscle tissue of Plagioscion squamosissimus and Colossoma macropomum from the Amazon region - Bittarello, Alis Correia [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Braga, Camila Pereira; de Paula Araújo, Wellington Luiz [UNESP]; da Cunha Bataglioli, Izabela [UNESP]; da Silva, Janaina Macedo [UNESP]; Buzalaf, Marília Afonso Rabelo; Fleuri, Luciana Francisco [UNESP]; de Magalhães Padilha, Pedro [UNESP] (Elsevier, 2019)
Mercury has the ability to bind to a variety of biomolecules, which can compromise its structure and functionality and thus promote its toxic effects. The aim of this study is to identify possible mercury biomarkers in muscle samples of Plagioscion squamosissimus (carnivorous fish) and Colossoma macropomum (omnivorous fish), from the Amazon region. The muscle proteome of fish species was separated by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE), and the total mercury concentrations in protein spots were determined by graphite furnace atomic absorption spectrometry (GFAAS). The protein spots containing mercury were characterized by electrospray ionization tandem mass spectrometry (ESI-MS/MS). The mercury concentrations in the protein spots were in the range of 1.10 ± 0.02–23.90 ± 0.33 μg g−1. The proteins phosphoglycerate mutase 2 (P. squamosissimus), hemoglobin β and cytochrome P450scc (C. macropomum), identified by ESI-MS/MS and showing the highest values of mercury concentration, may be considered possible mercury biomarkers.
Keywords: 2D PAGE; Bioaccumulation; Mercurial species; Xenobiotic